Line-based distributed coding scheme for onboard lossless compression of high-resolution stereo images - Jinlei Zhang; Houqiang Li (2013 IEEE International Symposium on Circuits and Systems (ISCAS), 2013)
On board compression coding of remote sensing images requires simple encoder and small storage, etc. However, the existing scheme such as JPEG2000 which is based on DWT has a complex encoder, and many algorithms based on DWT with a lower storage requirement have been researched. In this paper, we propose a novel line-based distributed lossless compression scheme for remote sensing stereo images with low storage costs and light complexity at the encoder. All the lines are encoded independently so that the required storage of the encoder is only one line. In order to achieve low encoding complexity, distributed coding techniques are used to exploit the spatial correlation and inter-view correlation of the stereo images. At the encoder, sub-sampled lines are successively encoded and transmitted. At the decoder, side information is generated with the knowledge of decoded sub-sampled lines and other previously decoded lines for the first view, and the second view will use the previous lines of the first view to remove the inter-view redundancy. In addition, line-based adaptive filter is performed to capture the spatial characteristics and template matching is used to remove the inter-view redundancy. Experimental results on high-resolution remote sensing stereo images demonstrate that the proposed scheme is comparable to JPEG2000 with respect to the compression performance, but with much lower encoding complexity and storage requirement.